The threshold effects of global economic uncertainty on foreign direct investment - Lagos, Konstantinos; Wang, Yuan (Transnational corporations, 2022)
This paper investigates the role of global economic uncertainty In Dunning's investment development path (IDP) framework. By applying the dynamic panel threshold model to data from 76 developed and developing countries, we find that countries' net outward investment (NOI) follows a non-linear pattern even after incorporating global economic uncertainty into the analysis. At the same time, global economic uncertainty has non-linear effects on NOI subject to the level of economic development. More importantly, our results show that NOI is path dependent, with correlation coefficients changing across the different stages of IDP, which implies that uncertainty affects countries' progression to the next stage of IDP differently. From a policy perspective, our findings call for special attention to policymakers in less developed nations. Even though global economic uncertainty may not always have a negative effect or may even improve a country's NOI for a while, it may deter the international expansion of local firms. In the presence of high global economic uncertainty, local firms are less likely to become outward foreign direct investors, which implies stagnation in internationalization.